Astrocamp : a proposed astronomical exploratorium and observatory camp in Clark Freeport Zone - Yambao, Charisse G. (Manila : National University, 2017)
The proposed project is Astrocamp: A proposed astronomical exploratorium and observatory camp, it is a place for the people especially the students to learn more about cosmic space. To stimulate hundreds of young minds to pursue career in science, technology and engineering and everyone can observe the celestial events. Also to develop concept for an astrocamp. In addition, to learn more about what are the facilities that are needed in an astrocamp so that it will be an entertaining and educational place for the interested people especially the students.
Acknowledgement -- Certificate of endorsement -- Approval sheet -- Table of contents -- List of tables -- List of figures -- List of graphs -- Abstract -- Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms and references -- Chapter 4. Data gathering, collation and analysis data -- Chapter 5. Design frameworks -- Chapter 6. Translation -- Bibliography -- Appendices.
Research Method : Qualitative Design.
Includes bibliographical references.